THE EFFECT OF PROBLEM BASED LEARNING AND GROUP INVESTIGATION LEARNING MODELS ON IPS LEARNING OUTCOMES - Arniaty Syarifuddin; Muhammad Nawir; Hidayah Quraish (Universitas Pakuan, 2023)
The aim of the study was to determine the difference in the effect of the Problem Based Learning and Group Investigation models on the interest and learning outcomes of Social Sciences Elementary School students in Region II, Barru District, Barru Regency. This type of research is pretest-posttest control group design. The number of samples in this study were 19 people, consisting of 15 people from the PBL class and 14 people from the GI class. The data collection method used was a learning achievement test to measure learning outcomes, a questionnaire to measure learning interest, and documentation. Data analysis techniques used are descriptive statistical approaches and inferential analysis, and hypothesis testing. The research results obtained were the Manova hypothesis test which was 0.189 0.05 which means that H1 was rejected Ho was accepted, that is, there was no difference in the PBL and GI models on interest, and social studies learning outcomes for elementary school students Region II, Barru District, Barru Regency. So it can be concluded that learning using the PBL and GI learning models can influence the interest and learning outcomes of social studies class V students, Barru District, Barru Regency